Expansão térmica de redes aleatórias de carbono - Ben, Julio (My University, 2017)
In this work, a simulation routine of carbon random networks, with variable hybridization, oriented to calculate the coeÿcient of thermal expansion, is presented. The method uses an algorithm for the generation of carbon random networks in addition to the quasi-harmonic approximation that, associated with the interatomic potential AIREBO, were used for the simulation. Using this approach, a set of 33 structures, composed of 32 atoms, with variable sp, sp2, sp3 carbon contents were generated and the respective volumetric thermal expansion coeÿcients were determined in a temperature range from 0 to 500 K. The results obtained suggest that, for this number of atoms per supercell, the coeÿcient of thermal expansion does not depend only on the percentage of carbon hybridization and, in principle, this is attributed to the thermodynamic limit of the system not being reached. Finally, it was possible to identify, in specific cases of structures where the percentages of sp2 carbon were maintained, that aspects such as the amount of sp carbon have influence on the coeÿcient of thermal expansion.
Neste trabalho, é apresentada uma rotina de simulação de redes aleatórias de carbono, com hibridização variável, orientada ao cálculo do coeficiente de expansão térmica. O método utiliza um algoritmo para geração de redes aleatórias de carbono além da técnica da aproximação quasi-harmônica que, associada ao potencial parametrizado AIREBO, foram empregados para a simulação. Utilizando esta abordagem, foi gerado um conjunto de 33 estruturas, compostas por 32 átomos, e com teores variáveis de carbono sp, sp2, sp3, para as quais determinou-se o coeficiente de expansão térmica volumétrico em um intervalo de temperatura de 0 a 500 K. Os resultados obtidos sugerem que, para este número de átomos por supercela de simulação, o coeficiente de expansão térmica não depende somente do percentual de hibridização do carbono e, em princípio, isto é atribuído ao limite termodinâmico do sistema não ter sido atingido. Por fim, foi possível identificar que, em casos específicos de estruturas onde foram mantidos os percentuais de carbono sp2, aspectos como a quantidade de carbono sp influenciam no coeficiente de expansão térmica.
Keywords: Carbono; Expansão (Calor); Carbon; Expansion (Heat)